A Study on English-Chinese Differences and Topological Transfer from the Perspective of Motion Events Construal - Haijie Wang (Ilmu Inovasi Nusantara, 2026)
Previous studies have consistently shown systematic differences in how motion events are construed in Chinese and English, particularly in terms of encoding manner, path, and figure–ground relations. However, the underlying causes of these differences and their implications for second language acquisition and instruction have not been fully synthesized. Addressing this gap is crucial, as motion event conceptualization reflects deeper typological and cognitive distinctions that may significantly influence learners’ interlanguage development. The primary objective of this study is to critically examine the roots, representations, and developmental tendencies of motion event construal differences between Chinese and English, and to explore how these differences affect second language learning and teaching. Specifically, the study aims to identify typological patterns and transfer effects observed in learners acquiring English as a second language. Methodologically, this paper employs a qualitative literature review approach, analyzing major theoretical frameworks and relevant empirical studies on motion event typology and second language acquisition. Data from previous experimental and corpus-based studies were carefully examined to identify recurring patterns of encoding and conceptualization. The findings reveal clear disparities between English and Chinese in the encoding of path and manner information, as well as in the conceptualization of figure–ground relations in motion events. Moreover, evidence indicates that contemporary Chinese shows a gradual tendency toward English-like motion event patterns. Importantly, the analysis confirms the presence of typological transfer, demonstrating that learners’ interlanguage increasingly aligns with the typological features of the target language as their L2 proficiency improves. The study further suggests that English–Chinese spatio-temporal conceptual differences may account for these disparities. These findings carry important implications for second language pedagogy, emphasizing the need for typology-informed instruction. Finally, the paper outlines current research limitations and proposes directions for future studies on motion event conceptualization and language learning